Identification of the variables causing the delay in changing channel IPTV service - State of the art (2012)
Currently, the IPTV service has been able to satisfy the expectation of entertainment and interactivity demanded by the market users, the proper performance of the service involves the solution to a set of challenges inherent IP environment, such as correction loss and delay information Multicast in the signal. This article reviews the most important techniques used to solve the delay in changing channel IPTV service cataloging solutions such as invasive or not, according to the form of bond equipment and / or multicast flows for such a solution. © 2012 IEEE.